Insect avoidance may override human disturbances in reindeer habitat selection - Skarin, Anna; Danell, Öje; Bergström, Roger; Moen, Jon (Rangifer, 2004)
Habitat selection of semi-domesticated reindeer (Rangifer tarandus tarandus) was investigated through faecal pellet- group counts and by direct observations of reindeer from helicopter in the Långfjället area in Idre reindeer herding district (62˚10’N) and in Mittådalen reindeer herding district (62˚50’N, aerial observations only). Reindeer pellets were found to be most abundant in habitats at high altitudes, and in some vegetation types. Pellet-group densities tended to be higher near the tourist trails, which often follow higher altitudes in the terrain. The aerial surveys showed that the reindeer moved towards higher altitudes when the wind speed was low and the temperature was high both in June and July. In June they moved towards lower regions when temperature was low and the wind speed was strong. The conclusion is that the reindeer use Långfjället to escape insect harassment and warm weather, even though disturbance by tourism sometimes is high. Abstract in Swedish / Sammanfattning: Habitatval hos tamren (Rangifer tarandus tarandus) undersöktes genom att göra en spillningsinventering och genom att göra flygobservationer från helikopter. Studien gjordes på Långfjället (62˚10’N) i Idre nya sameby och i Mittådalens samebys sommarbetesområde (62˚50’N, endast flygobservationer). På Långfjället finns det vandringsleder som är frekventerade av vandrare från juni månad fram till september. Spillningen visade att renarna föredrog höjderna i området samt en del av vegetationstyperna. Det var också mer spillning närmare vandringslederna. Detta kan förklaras av att vandringslederna följer höjderna i terrängen. Flyginventeringarna under både juni och juli visade att renarna rörde sig mot högre terräng när det var varmt och lugnt väder. I juni rörde dom sig också i lägre terräng när det var stark vind och kallt väder. Slutsatsen är att renarna väljer att vistas i högre terräng för att undvika störningar från insekter och för att finna svalka trots att det är mänsklig aktivitet i området.